Chemical Composition and Larvicidal Properties of Essential Oils from Wild and Cultivated Artemisia campestris L., an Endemic Plant in Morocco - Abdellatif Alami; Abdelhakim El Ouali Lalami; Saoussan Annemer; Fouad El-Akhal; Yassine Ez zoubi; Abdellah Farah (The Scientific World Journal)
The Asteraceae family is well known for its toxic and repellent activity against mosquitoes. In this study, essential oils (EOs) extracted from the aerial parts of both wild and cultivated Artemisia campestris L. plants were tested for larvicidal activity against Culex pipiens (Diptera: Culicidae), a pest mosquito widely suspected to be the vector responsible for West Nile virus transmission. The research aims at comparing the chemical composition and insecticidal activity of cultivated and wild A. campestris EOs. The EOs were obtained by hydrodistillation from the plant’s aerial parts and were analyzed using GC-MS. Furthermore, the larviciding experiment was carried out following the standard WHO protocol. The result showed that wild and cultivated plant EOs differed only quantitatively, while the qualitative profile revealed a nearly identical chemical composition. Camphor (18.98%), car-3-en-5-one (11.25%), thujone (6.36%), chrysanthenone (6.24%), filifolone (4.56%), and borneol (3.56%) dominate the wild plant EO. Camphor (21.01%), car-3-en-5-one (17%), chrysanthenone (10.15%), filifolone (7.90%), borneol (3.38%), and thujone (3.08%) are the major compounds of the cultivated plant. Cultivation did not affect the EO production since the yield of the cultivated plant was 0.5 ± 0.1% and 0.6 ± 0.2% for the wild plant. The cultivated A. campestris EO had the highest insecticidal activity (LC50 = 9.79 µg/ml), and no significant difference was noticed between wild and cultivated A. campestris EO in terms of LC90. These findings could pave the way for a new method of producing biocides to control major disease vectors and offer a potential alternative for pest control.